Basement‐Cover Relationships and Their Along‐Strike Changes in the Linking Zone (Iberian Range, Spain): A Combined Structural and Gravimetric Study. Issue 8 (14th August 2019) - Izquierdo‐Llavall, E.; Ayala, C.; Pueyo, E. L.; Casas‐Sainz, A. M.; Oliva‐Urcia, B.; Rubio, F.; Rodríguez‐Pintó, A.; Rey‐Moral, C.; Mediato, J. F.; García‐Crespo, J.
Abstract: Contractional deformation in the transition between the Iberian and Catalan Coastal Ranges (Linking Zone) generated both thin‐skinned structures detached in low‐strength Triassic units and basement‐involved structures. To evaluate their extent and relative contribution to the overall structure, we carried out a study combining structural geology and gravimetry. New gravity data (938 stations) and density determinations (827 samples) were acquired and combined with previous existing databases to obtain Bouguer anomaly and residual Bouguer anomaly maps of the study area. Seven serial and balanced cross sections were built, their depth geometries being constrained through the 2.5‐D gravity modeling and the 3‐D gravity inversion that we accomplished. The residual Bouguer anomaly map shows a good correlation between basement antiforms and gravity highs whereas negative anomalies mostly correspond to (i) Meso‐Cenozoic synclines and (ii) Neogene‐Quaternary basins. Cross sections depict a southern, thick‐skinned domain where extensional, basement faults inherited from Late Jurassic‐Early Cretaceous times were inverted during the Cenozoic. To the north, we interpret the existence of both Triassic‐detached and basement‐involved deformation domains. The two deformation styles are vertically overlapped in the southernmost part of the Catalan Coastal Ranges but relay both across and along strike in the Eastern Iberian Range. These basement and cover relationships and their along‐strike variations are analyzed in terms of the interplay between structural inheritance, its obliquity to the shortening direction, and the continuity and effectiveness of Triassic décollements in the study area. Key Points: From new and previous gravity data, we constructed Bouguer anomaly and residual Bouguer anomaly maps across the Linking Zone Gravity data are used to constrain depth geometries across seven, balanced cross sections Good correlation between residual gravity anomalies and basement geometries that are reconstructed through 3‐D gravity inversion